Pengembangan Media Canva Pada Fikih Bidayah Al-Mujtahid di Pondok Modern Al-Jauhar Riau: Analisis Aspek Validitas dan Praktikalitas - Rahmad Fadhli; Afif Hamzar; Rian Vebrianto (Musala : Jurnal Pesantren dan Kebudayaan Islam Nusantara, 2026)
This research addresses the lack of interactive learning media for the Bidayah Al-Mujtahid Fiqh course at Pondok Modern Al-Jauhar, Riau. The study aims to develop Canva-based learning media and evaluate its quality in terms of validity and practicality. Using the Research and Development (R&D) method with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation), data were collected through expert validation sheets and practitioner questionnaires. The results indicate that the developed Canva media is highly valid based on expert assessments of content and design. Furthermore, the media demonstrated excellent practicality for both teachers and students. In conclusion, Canva-based media is a valid and practical tool that effectively enhances the Fiqh learning process in Islamic boarding schools.